A Retrospective Study of Brain Metastases From Solid Malignancies: The Effect of Immune Checkpoint Inhibitors - Du, Wei; Sirbu, Cristian; Lucas, B. Daniel; Jubelirer, Steven J.; Khalid, Ahmed; Mei, Lin (Frontiers in Oncology, 2021)
Introduction: Brain metastases (BM) are associated with dismal prognosis and there is a dearth of effective systemic therapy. In this study, patients with BM from multiple solid tumors were identified from TriNetX databases, their clinicopathological features were evaluated, and the effects of immune checkpoint inhibitor (ICI) therapy were assessed. Methods: Variables, including median overall survival (OS), Eastern Cooperative Oncology Group (ECOG) performance status, primary diagnosis, and date of diagnosis, were retrieved from TriNetX, a real-world database. Kaplan-Meier plots and log-rank tests were applied to assess significance of differences in survival. Hazard ratio (HR) and 95% confidence interval (CI) values were calculated. All patient data were de-identified. Results: A total of 227,255 patients with BM were identified in the TriNetX database; median OS was 12.3 months from initial cancer diagnosis and 7.1 months from development of BM. OS of BM from non-small cell lung cancer (NSCLC), triple negative breast cancer (TNBC), melanoma and renal cell carcinoma (RCC) were 8.7, 14.7, 17.8, and 15.6 months, respectively. After matching patient baseline characteristics, OS of cohorts with or without exposure to ICIs was evaluated. For all types of cancer, median OS durations for the ICI and no-ICI cohorts were 14.0 and 7.9 months, respectively (HR: 0.88, 95% CI: 0.85–0.91). More specifically, OS was remarkably prolonged in patients with NSCLC (14.4 vs. 8.2 months; HR: 0.86, 95% CI: 0.82–0.90), TNBC (23.9 vs. 11.6 months, HR: 0.87, 95% CI: 0.82–0.92), and melanoma (27.6 vs. 16.8 months, HR: 0.80, 95% CI: 0.73–0.88) if patients had exposure to ICIs. In contrast, there was no significant difference in OS of patients with RCC treated with and without ICIs (16.7 vs. 14.0 months, HR: 0.96, 95% CI: 0.86–1.10). Conclusions: Overall, BM indicates poor patient outcome. Treatment with ICIs improves survival of patients with NSCLC, TNBC, and melanoma and BM; however, no significant improvement was observed in RCC. Investigations to identify prognostic features, oncogenomic profiles, and predictive biomarkers are warranted.